2008
DOI: 10.1111/1524-4725.2006.32009
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of and Risk Factors for Medical Malpractice Lawsuits among Mohs Surgeons

Abstract: Of the 300 completed surveys returned, 33 (11%) reported ever having been sued. Physicians who practiced Mohs surgery for a longer period of time were more likely to have been sued for malpractice. Physicians reported the wrong site and functional outcome as the most frequent causes of malpractice lawsuits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
32
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 16 publications
1
32
0
1
Order By: Relevance
“…Limited data have been published on wrongsite surgery in dermatology, but what is available suggests that dermatologists are at risk for this medical error. Perlis, Campbell, Perlis, Malik, and Dufresne (2006) reviewed malpractice cases involving Mohs surgeons and reported that 14% were filed because of wrong-site surgery. A review of adverse events in the Veteran's Administration showed that two of three events reported by dermatology were because of wrong-site surgery (Neily et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Limited data have been published on wrongsite surgery in dermatology, but what is available suggests that dermatologists are at risk for this medical error. Perlis, Campbell, Perlis, Malik, and Dufresne (2006) reviewed malpractice cases involving Mohs surgeons and reported that 14% were filed because of wrong-site surgery. A review of adverse events in the Veteran's Administration showed that two of three events reported by dermatology were because of wrong-site surgery (Neily et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…7,10,15,16 In fact, wrong-site surgery is one of the leading causes of medical malpractice lawsuits among Mohs surgeons. 17 This prospective study was performed to look at the incidence of patient difficulty with surgical site identification in Mohs micrographic surgery and to evaluate any contributing factors. Of the 333 cases evaluated, 9% of the patients were unable to confidently identify their surgical site on the day of Mohs micrographic surgery.…”
Section: Discussionmentioning
confidence: 99%
“…34 This correlates with improper performance of procedures having the second highest number of malpractice claims against dermatologists, 35 and WSS being the most common reason for claims against surgeons who perform MMS. 36 A recent survey of 150 dermatologists also revealed WSS to be the most frequent serious error encountered in their practice, with 21 instances reported. 2 To address these potential errors, JCAHO instituted the universal protocol in 2004, 37 consisting of a preprocedure verification process, marked procedure site, and time out before beginning a procedure.…”
Section: Wrong-site Surgery Key Pointsmentioning
confidence: 99%